Light Absorption and Photoluminescence Quenching Properties of Bulk Heterojunction Materials Based on the Blend of Poly(n-vinylcarbazole)/poly(n-hexylthiophen) - Phan, Long Dinh; Nguyen, Dinh Nang; Nguyen, Nam Phuong Hoai (Communications in Physics, 2019)
The enhancement of light absorption and photoluminescence quenching properties of the bulk heterojunction systems which were fabricated using poly(N-vinylcarbazole) (PVK); poly(N-hexylthiophene)(P3HT) and fullerene derivative 1-(3-methoxycarbonyl) propyl-1-phenyl-[6,6] C61 (PCBM) were investigated. The optimized material showed a broad absorption in the region from ultra violet to near infra-red and the luminescence quenching higher than 90%. The obtained results provide further insight into photophysics of the heterojunction system and device performance improvement by using this system as an active layer.